Case report: Vitamin B12 deficiency-associated hemolytic anemia - Sainatham, Chiranjeevi; Dy, Paul Stendahl; Kaushik, Sharanya; Tallapalli, Jayanth Reddy; Patel, Viral; Jindal, Vishal; Paul, Sonal (Frontiers in Hematology, 2024)
Vitamin B12 deficiency is commonly known to cause hematological, neurological, and gastrointestinal disturbances including anemia, pancytopenia, sub-acute combined degeneration, and glossitis, among others. Hemolytic anemia is a rare but possible presentation of vitamin B12 deficiency. We present a case series of three elderly females with different past medical histories but with similar presentations of severe anemia. Initial investigation revealed pancytopenia and hemolytic anemia. Further evaluation indicated vitamin B12 deficiency and subsequently, pernicious anemia, as confirmed by low serum vitamin B12 levels and positive intrinsic cell antibody respectively. These findings directed the diagnosis toward vitamin B12 deficiency-induced hemolytic anemia, a rare clinical entity. All three patients responded to treatment with intramuscular vitamin B12 injections, showing significant improvement in their pancytopenia and hemolytic anemia. This case series highlight the importance of considering vitamin B12 deficiency as a potential cause of hemolytic anemia in patients presenting with pancytopenia and ineffective hematopoiesis. Further research is necessary to illuminate the therapeutic implications of this rare condition.